Assessment of electrophile damage in a human brain endothelial cell line utilizing a clickable alkyne analog of 2-chlorohexadecanal - Nusshold, Christoph; Üllen, Andreas; Kogelnik, Nora; Bernhart, Eva; Reicher, Helga; Plastira, Ioanna; Glasnov, Toma; Zangger, Klaus; Rechberger, Gerald; Kollroser, Manfred; Fauler, Günter; Wolinski, Heimo; et al. (Free radical biology & medicine, 2016)
Peripheral leukocytes aggravate brain damage by releasing cytotoxic mediators that compromise blood–brain barrier function. One of the oxidants released by activated leukocytes is hypochlorous acid (HOCl) that is formed via the myeloperoxidase–H2O2–chloride system. The reaction of HOCl with the endogenous plasmalogen pool of brain endothelial cells results in the generation of 2-chlorohexadecanal (2-ClHDA), a toxic, lipid-derived electrophile that induces blood–brain barrier dysfunction in vivo. Here, we synthesized an alkynyl-analog of 2-ClHDA, 2-chlorohexadec-15-yn-1-al (2-ClHDyA) to identify potential protein targets in the human brain endothelial cell line hCMEC/D3. Similar to 2-ClHDA, 2-ClHDyA administration reduced cell viability/metabolic activity, induced processing of pro-caspase-3 and PARP, and led to endothelial barrier dysfunction at low micromolar concentrations. Protein-2-ClHDyA adducts were fluorescently labeled with tetramethylrhodamine azide (N3-TAMRA) by 1,3-dipolar cycloaddition in situ, which unveiled a preferential accumulation of 2-ClHDyA adducts in mitochondria, the Golgi, endoplasmic reticulum, and endosomes. Thirty-three proteins that are subject to 2-ClHDyA-modification in hCMEC/D3 cells were identified by mass spectrometry. Identified proteins include cytoskeletal components that are central to tight junction patterning, metabolic enzymes, induction of the oxidative stress response, and electrophile damage to the caveolar/endosomal Rab machinery. A subset of the targets was validated by a combination of N3-TAMRA click chemistry and specific antibodies by fluorescence microscopy. This novel alkyne analog is a valuable chemical tool to identify cellular organelles and protein targets of 2-ClHDA-mediated damage in settings where myeloperoxidase-derived oxidants may play a disease-propagating role. [Display omitted] •The synthesis of an alkyne analog (2-ClHDyA) of 2-chlorohexadecanal (2-ClHDA) is described.•2-ClHDyA compromises brain endothelial cell function similarly as 2-ClHDA.•Using click chemistry intracellular 2-ClHDyA-accumulating compartments are characterized.•Protein targets that are subject to 2-ClHDyA modification are identified by LC–MS/MS.